History of Aesthetic Control Management in Planning System, The Case of Turkey - Rezafar, Azadeh; Turk, Sevkiye Sence (International Planning History Society Proceedings, 2016)
History Aesthetic Control Regulations Turkey Urban Planning Abstract: Abstract Urban aesthetics is a complex subject in which the city needs to be evaluated beyond its physical characteristics. While the urban planning and design effects on the physical health of human, the city aesthetic effects on the human’s mental health. Aesthetic in urban areas has defined as beauty and the reflections of the beauty on the emotions of human. It is therefore perhaps surprising that the word "design, aesthetic" is not to be found in the Planning Acts. Why the aesthetic control managing in urban planning is unclear?. While contemporary planning theorists largely ignore the aesthetic issues, aesthetics and urban design have recently gained a central position within the practice of urban planning in all post-industrial countries. Actually design controls trace back in time to early settlement zoning but legalization of aesthetic control and its codifying attempts is not too old. The reason of this delay was skepticism approach of the courts to this issue. Because of individual property aspect of aesthetic control, many courts believed that nobody must deprive using of its own property. Aesthetic was considered as a luxury not necessity (Garvin & Leroy, 2003). As well as, too subjective issue of aesthetic didn’t need to be the basis of valid regulation in urban planning until 1930. By the time the law began to change and a few jurisdictions moved to accept aesthetic regulations for the reasons of public health, protection of property values, promotion of tourism and traffic. At the middle of 20 century, aesthetic regulations got place in the scope of general welfare and over time a majority of states allow design review based solely on aesthetic considerations. Zoning solely for aesthetic purposes is an idea, which its time has come and it is not outside the scope of the police power. As the construction market plays a substantial role in Turkey, and the country deserves to be an international logistics base with its location right between Europe, Middle East, Asia and Africa new attempts have done in order to deserve its location by enacting laws based on aesthetic issues. Turkey’s planning system has changed under the influential of European countries during the Ottoman Empire in the nineteenth century until the influences of American by Marshall Aid at 1950-1980 (Ayataç, 2007). Aesthetic has had an important position in all these planning systems and regulations directly or indirectly. In this article aesthetic programming according to Turkish urban planning system will be researched and regulations in connection with aesthetic issues will be evaluated. References: Garvin, E., A., Leroy, G., S., ‘Design Guidelines: The Law of Aesthetic Controls’, Land Use Law and Zoning Digest, April 2003, PP: 3-12 Ayataç, H.,‘The International Diffusion of Planning Ideas: The Case of Istanbul, Turkey’, JOURNAL OF PLANNING HISTORY / 2007, PP: 1-24